Heavy metals tolerance in oil-based drill cuttings contaminated soil planted with grass species - Otele, Ama; Ologidi, Charles Godspower; Tanee, Franklin Banakuna Godson; Agbagwa, Ikechukwu Ozoemenam (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
The prospect of selected grass species in phytoremediation of oily cuttings contaminated soil was investigated. The grass species were Panicum maximum, Pennisitum purpureum, Axonopus compressus, Heteropogon contortus, Andropogon gayanus, and Chloris virgata. Three levels of contamination were used; 50%, 25%, and 0%. The difference in the day of planting and harvesting was also considered. Furthermore, the growth stages of the grass species were looked at. The parameters assessed were copper, nickel, and zinc concentrations in soils and plant parts (roots and shoots), bioconcentration and translocation factors. The highest decrease of copper concentration in soil was achieved with mature P. purpureum and the least was with mature H. contortus at 25% contamination. Copper concentration in the shoot of A. compressus was significantly higher than the copper concentration in the shoot of the other species of grass. The highest copper concentration in roots was obtained with mature H. contortus and mature P. purpureum at 25% contamination. The highest reduction in soil nickel concentration was observed in mature and young P. maximum and mature P. purpureum and the least reduction was seen in young A. gayanus and young H. contortus at 25% contamination. The highest significant nickel concentration in the shoot was observed in young and mature A. compressus at 50% contamination. The lowest nickel concentration in roots was observed in young and mature P. purpureum. The highest zinc concentration reduction in soil was achieved with young and mature A. compressus, and young and mature P. purpureum at 25% contamination and the lowest reduction was obtained with young and mature C. virgata and young P. maximum. The highest concentration of zinc in the shoot was recorded in mature A. compressus at 25% contamination and lowest was observed in young A. gayanus, young P. maximum, and mature P. purpureum. Highest zinc concentration in roots was recorded in mature A. compressus and the lowest was observed in mature C. virgata at 25% level of treatment